Impact of antibiotics on membrane vesicle production in Group B Streptococcus - Macy E. Pell; Cole R. McCutcheon; Jennifer A. Gaddy; David M. Aronoff; Margaret G. Petroff; Shannon D. Manning (Microbiology Spectrum, 2025)
ABSTRACT Group B Streptococcus (GBS) is an important bacterial pathogen during pregnancy, colonizing up to 35% of pregnant people recto-vaginally. Intrauterine GBS infection during pregnancy can cause preterm labor, early membrane rupture, and, if the fetus gets infected, stillbirth or early-onset disease (EOD) following birth. Intrapartum antibiotics are recommended to treat GBS-colonized pregnant patients during labor to prevent these outcomes, particularly EOD. However, persistent GBS colonization has been observed despite antibiotic treatment. One strategy employed by bacteria to promote survival and antibiotic tolerance is the production of membrane vesicles (MVs). To understand how GBS MVs are affected by antibiotics and influence bacterial survival, we exposed a clinical GBS strain recovered from a pregnant patient with persistent colonization to antibiotics and examined the impact on MV production and composition. Using nanoparticle tracking analysis, microscopy, and proteomics, antibiotic treatment of GBS was found to significantly increase the production of MVs relative to untreated GBS (control) regardless of the antibiotic class (ampicillin; P = 4.2 × 10−6, erythromycin; P = 0.01). Moreover, antibiotic exposure yielded MVs with different protein composition compared to the untreated control, with 21 and 19 proteins unique to the ampicillin- and erythromycin-treated GBS, respectively. Increased abundance of antibiotic-specific protein targets was observed in the respective antibiotic-treated MVs, suggesting a mechanism for evading antibiotic-mediated killing. Together, these data suggest that antibiotic treatment alters both the production and composition of MVs, which can promote GBS survival in such conditions.IMPORTANCEGBS colonization during pregnancy can lead to invasive disease in neonates. Although antibiotics are given to GBS-positive pregnant patients during labor, some of these individuals remain colonized with GBS after treatment. Persistent GBS colonization is a public health concern, threatening the effectiveness of antibiotics and increasing the risk of GBS disease, especially for subsequent pregnancies. Although mechanisms linked to persistent colonization and antibiotic tolerance are poorly understood in GBS, MV production has been shown to promote bacterial survival in other species with and without antibiotic exposure. Herein, we demonstrated that two different antibiotics trigger changes in the production and composition of MVs in a persistent GBS colonizing strain, providing insight into the mechanisms used by GBS to rebound following antibiotic prophylaxis. Knowledge gained from this study can guide efforts in the development of more targeted and effective treatments for GBS disease.